2018
DOI: 10.1038/s41388-017-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

The ablation of the matricellular protein EMILIN2 causes defective vascularization due to impaired EGFR-dependent IL-8 production affecting tumor growth

Abstract: EMILIN2 is an extracellular matrix constituent playing an important role in angiogenesis; however, the underlying mechanism is unknown. Here we show that EMILIN2 promotes angiogenesis by directly binding epidermal growth factor receptor (EGFR), which enhances interleukin-8 (IL-8) production. In turn, IL-8 stimulates the proliferation and migration of vascular endothelial cells. Emilin2 null mice were generated and exhibited delayed retinal vascular development, which was rescued by the administration of the IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 55 publications
5
60
0
1
Order By: Relevance
“…The term matricellular has been applied to this group of extracellular proteins that do not contribute directly to the formation of structural ECM elements but serve to modulate cell–matrix interactions and cell function. While they usually have limited expression in adult life, they can become upregulated and released from the ECM during injury and repair . The production and release of matricellular proteins upon injury allows for binding of these proteins to a variety of receptors, growth factors and proteases in the capillary pericellular space, generally reducing cell adhesion and proliferation, and thus tuning ECM remodeling down (Fig.…”
Section: The Perivascular Extracellular Matrix As a Signaling Platformentioning
confidence: 99%
“…The term matricellular has been applied to this group of extracellular proteins that do not contribute directly to the formation of structural ECM elements but serve to modulate cell–matrix interactions and cell function. While they usually have limited expression in adult life, they can become upregulated and released from the ECM during injury and repair . The production and release of matricellular proteins upon injury allows for binding of these proteins to a variety of receptors, growth factors and proteases in the capillary pericellular space, generally reducing cell adhesion and proliferation, and thus tuning ECM remodeling down (Fig.…”
Section: The Perivascular Extracellular Matrix As a Signaling Platformentioning
confidence: 99%
“…In our study of EMILIN1, we observed significant links to tumor grades, overexpression in LGG and correlation between high-expression levels and poor OS and DFS. In some solid tumors, such as gastric cancer, breast cancer, EMILIN2 can play essential functions in the tumor microenvironment, affecting tumor growth by directly binding epidermal growth factor receptor (EGFR) and lymphangiogenesis (Marastoni et al, 2014;Paulitti et al, 2018). Paulitti et al (2018) confirmed that EMILIN2 have causes defective vascularization due to impaired EGFR-dependent IL-8 production affecting tumor growth.…”
Section: Discussionmentioning
confidence: 97%
“…In some solid tumors, such as gastric cancer, breast cancer, EMILIN2 can play essential functions in the tumor microenvironment, affecting tumor growth by directly binding epidermal growth factor receptor (EGFR) and lymphangiogenesis (Marastoni et al, 2014;Paulitti et al, 2018). Paulitti et al (2018) confirmed that EMILIN2 have causes defective vascularization due to impaired EGFR-dependent IL-8 production affecting tumor growth. Haage et al (2019) used bioinformatics analysis to identify EMILIN2 as a gene candidate distinguishing microglia from peripheral monocytes/macrophages in healthy and diseased cells.…”
Section: Discussionmentioning
confidence: 97%
“…In some solid tumors, such as gastric cancer, breast cancer, EMILIN2 can play essential functions in the tumor microenvironment, affecting tumor growth by directly binding epidermal growth factor receptor (EGFR) and lymphangiogenesis (Marastoni et al 2014;Paulitti et al 2018).…”
Section: Functional Enrichment Analysis Of Emilin/multimerins In Patimentioning
confidence: 99%
“…Paulitti, A et al (Paulitti et al 2018) EMILIN3 is a glycoprotein of the extracellular matrix missing the globular C1q domain (Schiavinato et al 2012). Zeng WJ et al (Zeng et al 2018) used bioinformatics analysis to study EMILIN3 as a prognostic gene in LGG, using genome-wide methylation and gene expression data.…”
Section: Functional Enrichment Analysis Of Emilin/multimerins In Patimentioning
confidence: 99%